(untitled) (Research, Society and Development, 2022)
Objective: To evaluate the initial forces generated by two types of palatal expansion appliances, through fiber optic sensors, in elastomeric models. Materials and Methods: An elastomeric model simulating the upper dental arch was fabricated. The sensors were placed adjacent to the first premolars and the first molars roots (apical, cervical, vestibular, palatal). Hyrax and Haas palatal expanders were fitted onto the dental arch. Activation of the screw was performed 4 times. The variations in wavelengths of each sensor during the activations were recorded. ANOVA and Games-Howell were used (P <.05). Results: In the first premolars, the force generated by Hyrax was higher than that generated by Haas in the cervical and apical regions of the palatal and vestibular surfaces, respectively; in the first molars, the force was higher in the cervical vestibular region than that in the cervical palatal region for both the appliances; in Hyrax, the force was higher in the apical vestibular than in the apical palatine in tooth 14 (P <.05). There was no difference between the devices for each activation; the total force generated by Hyrax was equal to that of Haas (P <.05). Conclusions: The fiber optic sensors were effective in measuring the initial forces generated by the studied palatal expanders. Hyrax and Haas palatal expanders produced similar forces. Greater force was recorded on the vestibular surfaces.